The Sacredness of Marriage and Declining Marriage Rates Among Youth - Deni Irawan; Abdul Rahman Ramadhan; Ruston Kumaini (Waraqat: Jurnal Ilmu-Ilmu Keislaman, 2025)
This research aims to analyse and discover the views of members of the Komunitas Mahasiswa Pecinta Ilmu (KMPI) Jember on the sacredness of marriage and the decline in marriage rates among young people, as well as the factors that cause KMPI Jember members to decide not to get married. Society, especially youth, no longer considers marriage as something sacred. Marriage is increasingly viewed merely as a biological imperative, achievable outside marital bonds. This view encourages the younger generation to be reluctant to get married. This research uses a qualitative approach. The criteria for the informants chosen in this study are members of KMPI Jember who are not married in the age category between 16 sixteen to 30 (thirty) years. The results of this research show that the views of KMPI Jember members on the sacredness of marriage include (1) something serious and full of responsibility, (2) irrelevant to current conditions and (3) influenced by religious and cultural education. KMPI Jember members' views on the decline in marriage rates among young people include (1) having a close relationship with social and cultural values, (2) being influenced by economic factors and (3) the role of education and career. Factors that cause KMPI Jember members to decide not to get married are (1) economic and emotional stability, (2) family and neighbourhood pressure and (3) education and career